Bibliometric Analysis of Islamic Money Market Research: Mapping Trends, Networks And Opportunities - Andriyanto, Gian Anggraeni; Mukti, Titania (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2024)
Islamic money market is part of short-term financial instruments. The development of Islamic money market is quite rapid in recent times. This study aims to map and analyze research trends on Islamic money market using bibliometric approach. Data sources were collected from the Scopus database using the search keyword "Islamic Money Market" totaling 204 documents. Data analysis was conducted using VOSviewer software and to identify research trends, collaboration networks, and influential publications. The results showed a significant growth trend in publications on Islamic money market, with research focus on topics such as risk management and market efficiency. The analysis also revealed a strong collaboration network between researchers and institutions across different countries, with Malaysia producing the most research on this theme. The researchers with the most publications are Masudul Alam Choudhury and Salina Kassim. The study also identifies research gaps and opportunities for future research, such as the development of innovative Islamic money market instruments, the integration of global Islamic financial markets, and the role of financial technology (fintech) in Islamic money markets. This research provides valuable insights for academics, practitioners, and policymakers to understand the Islamic money market research landscape and guide future developments in this area.